Polyvagal Theory: A Science of Safety - Stephen W. Porges; Stephen W. Porges (Frontiers in Integrative Neuroscience, 2022)
Contemporary strategies for health and wellbeing fail our biological needs by not acknowledging that feelings of safety emerge from internal physiological states regulated by the autonomic nervous system. The study of feelings of safety has been an elusive construct that has historically been dependent upon subjectivity. Acknowledging that feelings of safety have a measurable underlying neurophysiological substrate would shift investigations of feelings of safety from a subjective to an objective science. Polyvagal Theory provides an innovative scientific perspective to study feelings of safety that incorporates an understanding of neuroanatomy and neurophysiology. This perspective identifies neural circuits that downregulate neural regulation of threat reactions and functionally neutralize defensive strategies via neural circuits communicating cues of safety that enable feelings of safety to support interpersonal accessibility and homeostatic functions. Basically, when humans feel safe, their nervous systems support the homeostatic functions of health, growth, and restoration, while they simultaneously become accessible to others without feeling or expressing threat and vulnerability. Feelings of safety reflect a core fundamental process that has enabled humans to survive through the opportunistic features of trusting social engagements that have co-regulatory capacities to mitigate metabolically costly defense reactions. Through the study of neural development and phylogeny, we can extract foundational principles and their underlying mechanisms through which the autonomic nervous system leads to feelings of safety and opportunities to co-regulate. Several principles highlight the validity of a science of safety that when implemented in societal institutions, ranging from healthcare to education, would enhance health, sociality, and lead to greater productivity, creativity, and a sense of wellbeing. By respecting our need to feel safe as a biological imperative linked to survival, we respect our phylogenetic heritage and elevate sociality as a neuromodulator that functionally provides the scientific validation for a societal focus on promoting opportunities to experience feelings of safety and co-regulation.